Morpho-Anatomical Variations of Leaves Several Types of Betel Piperaceae in Durenan District, Trenggalek Regency - Mauludiyah, Nurhidayati Rofiah; Puspitawati, Rinie Pratiwi; Bashri, Ahmad (LenteraBio : Berkala Ilmiah Biologi, 2024)
The Piperaceae family is a plant species that has 3,700 species. In Durenan District, Trenggalek Regency, there are several species of Piperaceae family plants which have different leaf shapes. This study aimed to describe the morpho-anatomical variations of betel leaves in Durenan District, Trenggalek Regency. This study was a descriptive study to describe three types of betel; green betel, red betel, and china betel. Parameters measured were leaf morphology and leaf anatomy. Variations in betel leaf morphological characters from the Piperaceae family can be seen from leaf shape, leaf color, leaf base, petiole color, leaf length, leaf width, petiole length, and leaf area. Anatomical variations of betel leaf from the Piperaceae family included variations in the number of epidermal layers, the number of hypodermic layers, the number of palisade parenchyma layers, the number of spongy parenchyma layers, stomata shape, stomatal density, and stomata index.